2012
DOI: 10.1016/j.cbpa.2011.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Expression of aquaporin 3 in gills of the Atlantic killifish (Fundulus heteroclitus): Effects of seawater acclimation

Abstract: Estuarine fish, such as the Atlantic killifish (Fundulus heteroclitus), are constantly and rapidly exposed to changes in salinity. Although ion transport in killifish gills during acclimation to increased salinity has been studied extensively, no studies have examined the role of aquaglyceroporin 3 (AQP3), a water, glycerol, urea, and ammonia transporter, during acclimation to increased salinity in this sentinel environmental model organism. The goal of this study was to test the hypothesis that transfer from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 61 publications
2
26
2
Order By: Relevance
“…BW-native fish again trend towards a return to control expression levels in the hyper-osmotic challenge while expression in the FW-native fish did not recover to control levels. Similar responses of AQP3 have been observed in previous studies of F. heteroclitus (Jung et al, 2012;Whitehead et al, 2012b), as well as other species of killifish (Kozak et al, 2014;Whitehead et al, 2013). Together with regulation of VCAN, these data suggest divergence in RVI and RVD responses between the BW-native and FW-native populations.…”
Section: Differences Among Populationssupporting
confidence: 88%
“…BW-native fish again trend towards a return to control expression levels in the hyper-osmotic challenge while expression in the FW-native fish did not recover to control levels. Similar responses of AQP3 have been observed in previous studies of F. heteroclitus (Jung et al, 2012;Whitehead et al, 2012b), as well as other species of killifish (Kozak et al, 2014;Whitehead et al, 2013). Together with regulation of VCAN, these data suggest divergence in RVI and RVD responses between the BW-native and FW-native populations.…”
Section: Differences Among Populationssupporting
confidence: 88%
“…Multiple investigators have approached this question by localizing Aqp3 protein in gill tissue. In eel (Anguilla anguilla), killifish (Fundulus heteroclitus), and rainbow wrasse (Coris julis), Aqp3 immunoreactivity was observed in basolateral membrane of ionocytes (Lignot et al 2002, Brunelli et al 2010, Jung et al 2012. Here, we observed extensive Aqp3 immunoreactivity in ionocytes, mucous cells, and pavement cells of the afferent-vascular edges of FW filaments (Fig.…”
Section: :3mentioning
confidence: 48%
“…We and others have shown that branchial aqp3 expression in teleosts is rapidly modulated in response to changes in salinity, with elevated expression in FW versus SW , Lignot et al 2002, Tse et al 2006, Tipsmark et al 2010, Whitehead et al 2010, Jung et al 2012, Lam et al 2014, Madsen et al 2014, Moorman et al 2015. Prl has long been recognized as "the FW-adapting hormone" in fishes based upon its capacity to support branchial processes essential to life in FW (Hirano 1986, McCormick 2001.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the gene expression changes that enable this equalization occur more than 24 hrs after salinity transfer, the expression of core transporters such as Aqp3, Cftr, and subunits of NKA are upregulated more rapidly (McCormick et al, 2013). For instance, in the mummichog, mRNAs encoding aqp3 were observed to increase in abundance within 6 hrs of beginning a low salinity challenge (Jung et al, 2012).…”
Section: Discussionmentioning
confidence: 99%